Association of Health Information Literacy and Health Outcomes Among Individuals with Type 2 Diabetes and Metabolic Syndrome. - Wu, Kailu; Qi, Xiaoyan; Li, Aihua; Dong, Huan; Wang, Xiaojing; Ji, Meihua (Nursing Reports, 2025)
Objectives: Based on social cognitive theory, this study aims to explore the associated factors of and whether and how health information literacy was correlated to health behavior and glycemic control among individuals with type 2 diabetes and metabolic syndrome. Methods: Following convenient sampling, this cross-sectional, correlational study was conducted among 225 patients with type 2 diabetes and metabolic syndrome from an outpatient clinic in a suburban area of Beijing, China. Hierarchical multiple regression and mediation analysis were performed to explore the effect of health information literacy on self-management practice and hemoglobin A1c in this sample. The STROBE guidelines for cross-sectional studies were followed. Results: The findings showed incompetent health information literacy, inadequate self-management behavior, and suboptimal glycemic control in a sample of patients with type 2 diabetes and metabolic syndrome. Based on social cognitive theory, the results of regression analysis indicated that self-management attitude, health problem-solving, and chronic illness resources were correlated with self-management practice, and health problem-solving and health information evaluation were correlated with hemoglobin A1c. Mediation analysis revealed that self-management attitude, health problem-solving, and chronic disease resources fully mediated the effect of health information literacy on self-management practice. There was an indirect effect of health information literacy on hemoglobin A1c through health problem-solving. Conclusions: The findings demonstrated that health information literacy has significant indirect and direct effects on self-management behavior and glycemic control through self-management attitude, health problem-solving, and chronic disease resources in a sample of patients with type 2 diabetes and metabolic syndrome.